IMPLEMENTASI PENDIDIKAN KARAKTER ANAK PESERTA DIDIK PROGRAM UNGGULAN DAN REGULER DI SMP MUHAMMADIYAH 2 CIREBON - Al - Fafa, Ahmad Thariq; Masyitoh, Siti; Ashim; Duriyah (Al Naqdu, 2024)
This study explores the implementation of character education among students in the distinguished and regular programs at SMP Muhammadiyah 2 Cirebon. Utilizing a qualitative approach, the research evaluates the effectiveness of the character education program, identifies differences between the two programs, and examines their impact on students' moral and ethical development. The findings aim to provide insights for developing more holistic character education strategies within educational institutions.